DOUBLE KISSING (DK) CRUSH TECHNIQUE FOR THE TREATMENT OF COMPLEX PERIPHERAL DISEASE - Lopes, Alice Cabral (2022)
Introduction: The treatment of complex arterial lesions with long occlusions and involvement of the bifurcation of the tibial arteries remains a technical challenge in the endovascular area that often culminates in the choice of a conventional surgical alternative. Given the similarities in arterial caliber and necessary material, the adaptation of techniques used in lesions of bifurcations in the coronary circulation to the infrapopliteal territory has allowed a change in the treatment paradigm. Material and methods: This article presents a clinical case of a patient with complex peripheral arterial disease treated with the double kissing (DK) crush technique. Clinical case: 74-year-old male patient, hypertensive, and smoker, previously submitted to endovascular exclusion of infra-renal abdominal aortic aneurysm and bilateral saphenectomy, diagnosed with chronic limb-threatening ischemia of the left limb – Rutherford 4. AngioCT revealed a long (30 cm) femoropopliteal occlusion with rehabilitation at the level of the tibioperoneal trunk (TPT). Despite the extent and location of the lesion, the patient's surgical history, the absence of a great saphenous vein, and multiple previous femoral surgical approaches led the patient to be initially proposed for endovascular treatment using the DK crush technique. The lesion was recanalized through percutaneous access of the ipsilateral superficial femoral artery, and a guidewire was placed in the peroneal and posterior tibial arteries. The TPT bifurcation was predilated in kissing (1st kissing balloon), and a balloon-expandable stent (Xience Sierra® 3×18mm) was placed in the posterior tibialis (PT). Subsequently, a second balloon-expandable stent (Xience Sierra® 3.5×18mm) was placed in the peroneal artery with the consequent crush of the proximal portion of the 1st stent. The PT guidewire was removed and reintroduced through the stent mesh, and then the second kissing balloon of the bifurcation was performed, with an excellent angiographic result. Finally, femoropopliteal angioplasty was performed with placement of self-expanding stents (Zilver PTX®) in increasing degrees. The patient had no complaints and maintained patency of the entire arterial axis at nine months of follow-up, namely the peroneal and PT arteries, evident on the control ultrasound. Conclusion: In the case presented here, the adaptation of the DK crush technique to the tibial-peroneal territory allowed the effective revascularization of a complex arterial lesion, with good results in the medium term.